A time series perspective on income-based tax support for R&D and innovation - González Cabral, Ana Cinta (OECD Publishing, 2023)
The use of tax incentives that provide preferential tax treatment to the incomes arising from research and development (R&D) and innovation activities, such as intellectual property regimes, has accelerated over the last two decades. The globalisation of R&D together with the greater mobility of intangible income may have contributed to the rise in such incentives to attract and retain R&D and innovation activity while preventing the transfer of taxable base to other countries. This paper documents the changes to the availability and design of income-based tax incentives from 2000 onwards for 48 countries, including all OECD countries and EU countries. Building on this, the paper analyses trends in the generosity of income-based tax support over time by building indicators of effective tax rates that can provide insights into the impact of Action 5 of the OECD/G20 Base Erosion and Profit Shifting project
Keywords: Finance and Investment; Taxation; Science and Technology